Recent Progress in Proximity Coupling of Magnetism to Topological Insulators. Issue 33 (29th June 2021) - Bhattacharyya, Semonti; Akhgar, Golrokh; Gebert, Matthew; Karel, Julie; Edmonds, Mark T.; Fuhrer, Michael S.
Abstract: Inducing long‐range magnetic order in 3D topological insulators can gap the Dirac‐like metallic surface states, leading to exotic new phases such as the quantum anomalous Hall effect or the axion insulator state. These magnetic topological phases can host robust, dissipationless charge and spin currents or unique magnetoelectric behavior, which can be exploited in low‐energy electronics and spintronics applications. Although several different strategies have been successfully implemented to realize these states, to date these phenomena have been confined to temperatures below a few Kelvin. This review focuses on one strategy: inducing magnetic order in topological insulators by proximity of magnetic materials, which has the capability for room temperature operation, unlocking the potential of magnetic topological phases for applications. The unique advantages of this strategy, the important physical mechanisms facilitating magnetic proximity effect, and the recent progress to achieve, understand, and harness proximity‐coupled magnetic order in topological insulators are discussed. Some emerging new phenomena and applications enabled by proximity coupling of magnetism and topological materials, such as skyrmions and the topological Hall effect, are also highlighted, and the authors conclude with an outlook on remaining challenges and opportunities in the field. Abstract : The magnetic proximity effect in topological insulator–magnetic materials heterostructures is a promising strategy to optimize new topological phases with potential applications in low‐energy electronics. Progress in this field is summarized with an introduction to the underlying physical mechanisms, a review of emerging material systems for magnetic proximity in topological insulators, and the status and prospects for obtaining new topological phases.